Évanescence du joi et joie de l’évanescence : éthique et esthétique courtoises dans le Roman de la Rose de Jean Renart - Corinne Cooper (Revue des Langues Romanes)
Jean Renart’s Roman de la Rose, or Guillaume de Dole, seems to propose a narrative rewriting of the theme of distant love. However, the experience of joi, which is at the heart of the love poetry of the troubadours and of the theme of love from afar, seems singularly absent from this fairy-tale-like novel. Would the narrativization of joi lead to its dulling? An analysis of the link between curial rhetoric, amorous feeling and literary practice in Jean Renart’s text, around the idea of gap, play, non-coincidence, perhaps invites us to rethink the relationship of this novel with its hypotext and thus to question the links between joy, literary seduction, and the construction of a courtly ideal.